Answers

2014-06-07T16:49:42+08:00
Use the formula: 
y=a x^{2} +bx+c

a x^{2} (quadratic term)
bx (linear term)
c (constant)

Ex.
3x-2 x^{2} =7

-2 x^{2} +3x=7 or -1(-2 x^{2} +3x = 7) -> 2 x^{2} -3x=-7

Just do the same thing to the other equations. But before you change it to standard form remember to simplify it. Good luck :)
Click "thanks" if I helped. It'll be appreciated. :)


1 5 1
i can understand im so very confused
That's contradicting, You can understand but you're confused? Or is it a typo... If yes I'll elaborate it thoroughly. :)
please elaborate it or please answer all the number questions PLEASE
how about the others?? please answer it to me
The Brainliest Answer!
2014-06-07T17:03:48+08:00
The standard form of quadratic equation is ax^2 + bx + c = 0
where a, b and c are constant values. 
example:
 2x^{2}+5x+3=0
In this one a=2b=5 and c=3

so in no. 1. 3x-2 x^{2} =7
Answer:
1.2 x^{2} -3x+7=0

so your answer should be in this form:
a x^{2} +bx+c=0
1 5 1
ohh THANK YOU
how about the others??
Ohh that's quite a lot it is easy to solve but hard to type it.
answer it and leave those you find hard to solve and I can solve it for you..